2014
DOI: 10.1111/jzo.12129
|View full text |Cite
|
Sign up to set email alerts
|

Fish in space: local variations of home range and habitat use of a stream‐dwelling fish in relation to predator density

Abstract: A key response of animals to local environmental variation is altered use of space, but studies simultaneously examining local variation in habitat use and space use are uncommon. We predicted that elevated abundance of avian predators would result in grayling Thymallus thymallus, a stream‐dwelling fish, using mesohabitats containing more cover, superimposed on seasonal changes in use of key resources (and hence space use) for functions such as reproduction. Using radio‐telemetry, the pattern of space and habi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
2
0
0
1
Order By: Relevance
“…thymallus , suggesting that they are able to recognize favourable conditions and react to changes in specific environmental factors effectively. As was recently observed by Lucas & Bubb (), wild T . thymallus adjust their activity to the elevated predation risk as well.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…thymallus , suggesting that they are able to recognize favourable conditions and react to changes in specific environmental factors effectively. As was recently observed by Lucas & Bubb (), wild T . thymallus adjust their activity to the elevated predation risk as well.…”
Section: Discussionsupporting
confidence: 82%
“…This study shows threshold behavioural response in wild T. thymallus, suggesting that they are able to recognize favourable conditions and react to changes in specific environmental factors effectively. As was recently observed by Lucas & Bubb (2014), wild T. thymallus adjust their activity to the elevated predation risk as well. This study also revealed behavioural deficits of hatchery-reared T. thymallus in the wild; hence, in attempts to conserve indigenous T. thymallus populations, restoration of habitat complexity and natural spawning should take precedence over stocking.…”
Section: Discussionsupporting
confidence: 67%
“…Desde a década de 1950, porém, o assunto tem sido estudado por diversos autores, especialmente na América do Norte (e.g. Funk 1957, Crossman 1977, Todd & Rabeni 1989, Young 1996, Horton & Guy 2002, Lucas & Bubb 2014, que apontaram evidências de movimentos em peixes de riacho, embora apenas recentemente o tema tenha sido investigado na região Neotropical (e.g. Mazzoni & Iglesias-Rios 2012, Espírito-Santo et al 2016, Celestino et al 2017, Azevedo 2017, Barros 2017, Espírito-Santo et al 2018, Lima 2018, Mazzoni et al 2018, Henninger et al 2020, De Fries 2020.…”
Section: Conclusõesunclassified